Toxinogenicity and markers of pathogenicity of Pseudomonas aeruginosa strains isolated from patients with tumor diseases - Majtán, V; Hostacká, A; Majtánová, L; Trupl, J (Folia microbiologica, 2002)
Potential virulence factors (elastase, proteinase, lipase, phospholipase C, alginate) as well as surface properties (hydrophobicity, motility) were determined in 103 Pseudomonas aeruginosa strains isolated from patients with cancer. Nontypable strains were the dominant group (60%), followed by serotypes O11 (17%), O12 (7%) and O4 (5%). Seventy-one strains (69%) produced high level of elastase (10-60 mg/L), 87% of the strains possessed high activity of proteinase (bacterial) (10-250 mg/L) and 69% of the strains demonstrated higher level of lipase (20-150 U/mL); these elevated levels of enzymes were associated mainly with nontypable strains. On the other hand, 79% of the strains did not produce or produced only a low level of phospholipase C and 60% of isolates did not manifest any or very low production of alginate. Hydrophobicity demonstrated by adherence of the bacteria to xylene was shown by 69% of strains; 94% of strains aggregated with ammonium sulfate. Motility in the range of 31-80 mm was found in 76 strains (74%). The considerable virulence of tested P. aeruginosa strains was confirmed. The nontypable strains manifested the most frequent group with high level of elastase, proteinase, lipase, hydrophobicity and motility.
Keywords: lipasa; Opportunistic Infections; lidé; Lipase; Hexuronic Acids; Virulence; fosfolipasy typu C; Pseudomonas aeruginosa; sérotypizace; endopeptidasy; bakteriální adheze; Alginates; Pseudomonas Infections; kyselina glukuronová; virulence; kyseliny hexuronové; Humans; oportunní infekce; Type C Phospholipases; Bacterial Adhesion; Glucuronic Acid; nádory; Pancreatic Elastase; pankreatická elastasa; pseudomonádové infekce; Endopeptidases; algináty; Neoplasms; Serotyping